MENINGKATKAN PEMAHAMAN KONSEP BILANGAN BULAT MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TGT MENGGUNAKAN MEDIA POTAKA PESERTA DIDIK KELAS V SDN DERMO - Sa'diyah, Nur Halimatus; Uchtiawati, Sri; Sari, Arissona Dia Indah (JTIEE (Journal of Teaching in Elementary Education), 2020)
This type of research uses classroom action research. Consists of 2 cycles, namely: planning, implementation, observation and reflection. The subject chosen by the researcher is the fifth grade student of SDN Dermo-Benjeng-Gresik, the academic year 2018/2019 which amounts to 15 students. The results of this study showed that in the first cycle 1 the observation of the activities of students averaged 51,43% and in the second cycle II became 75,33%. While the results of the concept understanding test in the first cycle I the classical average value of 53% and in the second cycle II the average value was 80%. In the crease occurred because of improvement in the second cycle II by making learning more interesting. Based on the results of the study it can be concluded that using the cooperative type TGT models and POTAKA media can improve the understanding of concepts on mathematics subjects in class V SDN Dermo integer material.